2019
DOI: 10.1038/s41698-019-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mucosal Dysbiosis of Early Colonic Neoplasia

Abstract: Aberrant crypt foci (ACF) are the earliest morphologically identifiable lesions in the colon that can be detected by high-definition chromoendoscopy with contrast dye spray. Although frequently associated with synchronous adenomas, their role in colorectal tumor development, particularly in the proximal colon, is still not clear. The goal of this study was to evaluate the profile of colon-adherent bacteria associated with proximal ACF and to investigate their relationship to the presence and subtype of synchro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…These findings suggest that biomarkers based on the oral microbiota may help predict the risk of CRA and CRC. Hong et al found that microbiome dysbiosis in early aberrant crypt foci legion can be used as a biomarker for potential CRC development 55 . However, colonoscopy used in the study of Hong is an invasive method, whilst oral swab in our study is non-invasive that makes patients more compliant.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that biomarkers based on the oral microbiota may help predict the risk of CRA and CRC. Hong et al found that microbiome dysbiosis in early aberrant crypt foci legion can be used as a biomarker for potential CRC development 55 . However, colonoscopy used in the study of Hong is an invasive method, whilst oral swab in our study is non-invasive that makes patients more compliant.…”
Section: Discussionmentioning
confidence: 99%
“…Even though fecal microbiota partially reflects the microbiota at the mucus layer, differences between fecal and tissue microbiota are still evident. The bacterial clusters in IVF may provide greater insight into mucosal-specific colonic neoplasia due to their close interactions with epithelial and immune cells (Hong et al, 2019). As there is no unanimous conclusion in the advantages of different types of specimens, accurate comparisons between sample types in large sample sizes are needed, and a combinatorial approach may enable a sensitive and accurate evaluation of the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…66 A positive correlation between Ruminococcus gnavus and KRAS mutation in aberrant crypt foci samples was also described, although this finding was only reported in one study with a limited sample size. 69 As described previously, serrated neoplasia is characterized by high MLH1 deficiency, KRAS and BRAF mutation, 6,11,25,27 yet the association with F. nucleatum, B. fragilis, or R. gnavus remains unclear and needs to be explored in future studies.…”
Section: Gut Microbiota and Specific Molecular Featuresmentioning
confidence: 94%